Analisis Hukum Perlawanan Pihak Ketiga Selaku Pemilik PPJB terhadap Sita Umum Boedel Pailit - Sarah Faizurah Khairunisa; Elisatris Gultom; Aam Suryamah (Syntax Corporation Indonesia, 2024)
Third-party objections to seizure are a form of gugatan lain-lain regulated by Article 3, paragraph (1) of UU No. 37 Tahun 2004 about Kepailitan dan PKPU. A common issue in these third-party objections involves land sold through Perjanjian Pengikatan Jual Beli (PPJB) without making Akta Jual Beli (AJB). In practice, there is a disparity in the decisions related to disputes involving land transactions through PPJB, leading to legal uncertainty and questioning the validity of PPJB as a legitimate document. This study aims to contribute to understanding the position of third parties in opposing general seizures in bankruptcy cases and to provide practical insights for those involved in similar legal processes. The methodology employed is normative juridical, analyzing secondary sources as the primary material. The approach used includes statue and case approaches. The research findings indicate that third parties in bankruptcy cases can still file objections to assert their rights to land even after the lapse of five years through gugatan lain-lain. Additionally, PPJB can legally serve as evidence of the transfer of land rights involved in a case, provided that the buyer has fully paid for the land and acted in good faith.